Land’s batuques, sea’s rhythms: musical expressions and cultural connections in the north of Mozambique (centuries XIX-XXI) - Mattos, Regiane Augusto de (2019)
The main objective of this article is to analyze the historical and cultural connections between the societies of northern Mozambique and those located in the Indian ocean through musical expressions, their uses and transformations between the 19th and 21st centuries. Starting from the batuques of the Makua populations, batuques of reua, maulides and dtiqiri of the Muslim brotherhoods until the tufo, it is tried to approach some aspects, such as the forms of organization around the relations of gender, kinship and control of the land and the presence of Islam, fundamental to understand the history of these societies.